The First 24 Hours Post Partum Mother’s Breast Milk Production at Hospital - Kustriyani, Menik; Wulandari, Priharyanti (University of Muhammadiyah Semarang, 2020)
Breast milk is ideal baby food, various kinds of breast milk content are needed by the baby. Factors affecting breastmilk production among others: mother's food intake, mind, physiological anatomy, baby suction factors, rest factors and drug factors. The purpose of this study was to determine the production of postpartum mother milk in the first 24 hours. The research was conducted in descriptive quantitative with a time-series approach. The research subjects were obtained through consecutive sampling. Data were obtained at 2 hours postpartum, 16 hours postpartum and 24 hours postpartum using measuring cups and observation sheets. The subjects of this study were 21 normal postpartum mothers. The research data were analyzed using univariate analysis. The study was conducted in July 2020 at Ungaran Hospital. Respondents have explained the study. Researchers guarantee the confidentiality of respondents from the beginning to the end of the study. The results showed parity of postpartum multiparous mothers was 52.4%, primiparous 47.6%. Postpartum mothers with the early adult category were 66.7%. Postpartum mother breastmilk production at 2 hours with an average ± 0.155 cc, the mother experienced an increase in the amount of milk production at 16 hours postpartum by an average of ± 1.272 ml and at 24 hours postpartum experienced an increase in the amount of mother's milk production on average ± 1.369 ml. It can be concluded that physiologically normal post-partum mother milk production has increased gradually, the increase is because the more often the mother empties the breast, the more breast milk production.